Blog Development as A Resource for Geographic Learning in SMAN Kecamatan Percut Sei Tuan - Hasri, Annisa; Berutu, Nurmala; Rahmadi, M Taufik (Indonesia University of Education, 2021)
An effective learning process is a learning process that uses various forms of learning resources. This study aims to determine blogs' feasibility as a source of learning geography for material management of Indonesia's natural resources at SMAN Percut Sei Tuan District. This research was conducted in the odd semester of the 2019/2020 school year, with a population of all class XI IPS students at SMAN 1 Percut Sei Tuan consisting of 4 classes with a total of 139 students and class XI IPS at SMAN 2 Percut Sei Tuan which consisted of 2 courses with the number of 69 students. The study sample was class XI IPS 1 at SMAN 1 Percut Sei Tuan, totaling 35 students, and class XI IPS 1 at SMAN 2 Percut Sei Tuan amounted to 33 students. This research is development research using the Borg and Gall model with ten steps of research implementation. The data collection technique used was a questionnaire. The data analysis technique used is descriptive. The results showed that the validation of the feasibility of blogs as a source of learning geography carried out in 2 stages showed that in the first stage of verification, the acquisition of the feasibility of a blog as a source of learning geography was (87.27%) with criteria worthy of revision as needed. After making improvements according to the assessors' input, the results of the stage 2 validation obtained the feasibility of a blog as a source of learning geography (93.89%) with very feasible criteria without revision.